Tantangan dan Implikasi Tampilan Agama di Media: Mengkaji Respons Masyarakat dan Dampak Sosial Politik - Rokibullah, Rokibullah; Hidayatulloh, Cecep (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In the digital era, media plays a significant role in shaping public views on religion. Since the advent of the internet, religious information has become more easily accessible, but this has also led to various reactions from the public, both positive and negative. This study aims to understand the public's response to the representation of religion in various media and its influence on their religious understanding. This research uses a descriptive qualitative method. The results and discussion show that media has a great influence in spreading religious teachings, shaping perceptions, and influencing religious practices. There are diverse public attitudes, categorized as conservative, moderate, and liberal, each with a different response to religious content in the media. Social media, in particular, poses new challenges such as the "celebrity preacher" phenomenon and the spread of misinformation. In conclusion, media has a dual role: as an effective tool for disseminating religious teachings and as a medium with the potential to spread polarization and superficial understanding. To ensure a positive impact, it is necessary to present quality content, adhere to media ethics, and enhance media literacy among the public.